Dynamics of Mathematical Attitude and Academic Motivation: Insights from School Students - Mirgank, Kislay Kishor; Kalhotra, Satish Kumar (PT. Riset Press International, 2025)
This study delves into the intricate relationship between mathematical attitude and academic motivation among secondary school students, aiming to provide insights crucial for educational practitioners and policymakers. Through a descriptive cum survey method, 100 7th-grade students from Jiya Lal High School in Barauni, Bihar, were meticulously selected, ensuring diversity across genders and geographic locations. Researchers assessed students' attitudes and motivations using the Attitudes Towards Mathematics and Academic Motivation Scales. Statistical analyses revealed no significant differences based on gender or location, suggesting the influence of other factors. Moreover, the lack of correlation between mathematical attitude and academic motivation underscores their independent nature. Interaction effects of gender and location on these constructs were negligible, indicating the dominance of other variables. This study highlights the need for nuanced interventions, focusing on socioeconomic status, cultural background, and educational experiences rather than demographic factors alone. Embracing a holistic approach in educational support systems, including counselling services and culturally responsive teaching practices, is crucial for fostering positive academic attitudes and motivations among students. This research enhances educational practices and interventions tailored to diverse student populations, ultimately promoting academic success in mathematics and beyond.